A comparison between predetermined and self-selected approaches in resistance training: effects on power performance and psychological outcomes among elite youth athletes - Kevin Watson; Israel Halperin; Joan Aguilera-Castells; Antonio Dello Iacono (PeerJ, 2020)
Background The aim of this study was to investigate if choice over resistance training exercise order affects motor performance and psychological outcomes among elite youth hockey players. Methods Seventeen elite hockey players (male, n = 14; female, n = 3, age: 15.1 ± 1.1 years) participated in this study. In the first session, individual optimum power loads were calculated in the back squat, jump squat, bench press and bench throw exercises. Then, in four counterbalanced sessions, participants completed three sets of six repetitions in the same exercises loaded with their optimum power loads. In two sessions, athletes used a self-selected order of exercises, while in other two sessions the order was predetermined. Power outputs were estimated with a linear position transducer. Fatigue and enjoyment were measured during and after the sessions using standardized questionnaires. Repeated measures analyses of variance and a paired-sample t-test were used to compare the effects between conditions. Results We observed trivial to small differences between conditions in power outputs (p ≥ 0.07; ES ≤ 0.21), fatigue (p ≥ 0.42; ES ≤ 0.33) and enjoyment (p = 0.72; ES = 0.05). Conclusion Given the comparable effects between approaches, both can be used when coaching youth athletes. Self-selecting the order of exercises based on preferences is a feasible and practical coaching option when working with youth athletes.